2013
DOI: 10.1161/atvbaha.113.302030
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Inhibition of Phospholipase D Protects Mice From Occlusive Thrombus Formation and Ischemic Stroke—Brief Report

Abstract: Objective-We recently showed that mice lacking the lipid signaling enzyme phospholipase (PL) D1 or both PLD isoforms (PLD1 and PLD2) were protected from pathological thrombus formation and ischemic stroke, whereas hemostasis was not impaired in these animals. We sought to assess whether pharmacological inhibition of PLD activity affects hemostasis, thrombosis, and thrombo-inflammatory brain infarction in mice. Approach and Results-Treatment of platelets with the reversible, small molecule PLD inhibitor, 5-fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 28 publications
6
46
0
2
Order By: Relevance
“…Although small molecule PLD inhibitors appear to have some value in cell culture systems, their usefulness for PLD inhibition in vivo in animal models is less well established. Recent studies have shown that pharmacologically and genetically induced PLD inhibition had no obvious side effects (8,11); thus, such a safe therapy could be particularly advantageous in clinical practice. Accordingly, highly selective PLD inhibitors with greater potency need to be developed and analyzed to enable optimized drug delivery and bioavailability.…”
Section: Role Of Pld Up-regulated In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Although small molecule PLD inhibitors appear to have some value in cell culture systems, their usefulness for PLD inhibition in vivo in animal models is less well established. Recent studies have shown that pharmacologically and genetically induced PLD inhibition had no obvious side effects (8,11); thus, such a safe therapy could be particularly advantageous in clinical practice. Accordingly, highly selective PLD inhibitors with greater potency need to be developed and analyzed to enable optimized drug delivery and bioavailability.…”
Section: Role Of Pld Up-regulated In Cancermentioning
confidence: 99%
“…The PLD signaling pathway provides a possible molecular link between inflammation and cancer; however, systematic investigation of PLD as a therapeutic target has only begun within the last few years with the development of small molecule PLD inhibitors and PLD knock-out mice (5)(6)(7)(8)(9)(10)(11)(12)(13). This review covers recent advances in the regulation of PLD expression and its role in cancer and inflammation.…”
mentioning
confidence: 99%
“…To date, the inhibitors have not been associated with off-target or nonspecific effects, excepting one of the PLD1-selective compounds (66). FIPI has also been employed in vivo to study cancer growth and metastasis and platelet activation (22,35,67), which was achievable given its 5.5 h half-life and acceptable bioavailability and solubility (54). The subtypespecific PLD inhibitors currently available are less amenable for in vivo studies with shorter half-lives (45 min to 1 h) and efficient first-pass clearance (56), but with continued development could become invaluable tools for study in animal models and as potential therapeutics.…”
Section: Tools Used For Study Of Pld Functionmentioning
confidence: 99%
“…Roles for PLD2 in thrombotic disease ( 37,66 ), cancer ( 67, 68 ), Alzheimer's disease (AD) ( 69 ), and immune function ( 65 ), based on animal model studies, have recently been summarized ( 5 ). Other potential functions have been raised by tissue culture studies, some of which will be reviewed here.…”
Section: Pld2mentioning
confidence: 99%
“…Roles for PLD1 in thrombotic disease ( 28,37,38 ), cancer ( 39 ), and auto-immunity ( 40 ), as revealed through animal model studies, have recently been summarized ( 5 ). Many other possible roles are suggested by cellular studies that have not yet been addressed in vivo, some of which will be reviewed here.…”
Section: Pld1mentioning
confidence: 99%